Implementation of Counseling and the Effect of Counseling Results in Adjudicating Marriage Dispensation Applications at the Martapura Religious Court Class I B - Abdul Haris; Dr.Budi Rahmat Hakim, MHI; Farihatni Mulyati, MHI; Inawati, Lc.,MA (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract The objectives of this research are to understand the counseling implementation by PUSPAGA at the Martapura Religious Court and to ascertain the impact of counseling outcomes given by PUSPAGA on judges' deliberations in adjudicating marriage dispensation requests. This study employs an empirical research design utilizing a qualitative approach, generating descriptive data. The research is conducted at the Martapura Religious Court Class IB. The counseling process takes place after the parents of the couple submit a Marriage Dispensation request to the Religious Court. Subsequently, they are directed to undergo counseling at PUSPAGA, which is scheduled at the Religious Court. Those who submit requests outside the schedule either wait for the designated days or visit the office of the Department of Social Affairs, Women's Empowerment, Child Protection, Population Control, and Family Planning of Banjar Regency to obtain a counseling outcome letter, which is a requirement for the acceptance and processing of the request. The counseling outcomes provided by PUSPAGA to the panel of judges do not significantly influence their decisions to grant or deny dispensation, as the counseling outcomes, which are in the form of minutes of the session, do not hold substantial weight in court proceedings. However, if the counseling outcomes include recommendations regarding the suitability of marriage based on PERMA No. 5 of 2019, these recommendations can significantly impact the judges' decisions to approve or reject the marriage dispensation requests. Keywords: Counseling, Marriage, Marriage Dispensation Request, Martapura Religious Court. Abstrak Penelitian ini bertujuan untuk mengetahui pelaksanaan konseling oleh PUSPAGA di Pengadilan Agama Martapura dan untuk mengetahui pengaruh hasil konseling yang diberikan oleh PUSPAGA terhadap pertimbangan hakim dalam mengadili permohonan dispensasi nikah. Penelitian ini menggunakan desain penelitian empiris dengan menggunakan pendekatan kualitatif dan menghasilkan data deskriptif. Penelitian dilakukan di Pengadilan Agama Martapura Kelas IB. Proses konseling dilakukan setelah orang tua dari pasangan tersebut mengajukan permohonan Dispensasi Kawin ke Pengadilan Agama. Selanjutnya, mereka diarahkan untuk menjalani konseling di PUSPAGA yang sudah terjadwal di Pengadilan Agama. Bagi mereka yang mengajukan permohonan di luar jadwal tersebut, dapat menunggu hari yang telah ditentukan atau datang ke kantor Dinas Sosial, Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana Kabupaten Banjar untuk mendapatkan surat hasil konseling yang menjadi syarat diterimanya dan diprosesnya permohonan tersebut. Hasil konseling yang diberikan oleh PUSPAGA kepada majelis hakim tidak terlalu berpengaruh terhadap keputusan untuk mengabulkan atau menolak permohonan dispensasi, karena hasil konseling yang hanya berupa berita acara tidak memiliki kekuatan hukum yang signifikan dalam persidangan. Namun, jika hasil konseling tersebut memuat rekomendasi mengenai kesesuaian pernikahan berdasarkan PERMA No. 5 Tahun 2019, maka rekomendasi tersebut dapat secara signifikan mempengaruhi keputusan hakim untuk mengabulkan atau menolak permohonan dispensasi nikah. Kata kunci: Konseling, Perkawinan, Permohonan Dispensasi Kawin, Pengadilan Agama Martapura.